STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PENGUATAN MODERASI BERAGAMA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP - Zuhroh, Neng Enab Siti; Fitriyani Kosasih (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The strengthening of religious moderation values in schools is crucial from an early age to prevent extremist and intolerant views. School principals play a strategic role in fostering an inclusive, tolerant, and diversity-appreciative school culture. This study aims to describe the transformational leadership strategies of school principals in reinforcing religious moderation through Islamic Religious Education (PAI) learning. Using a qualitative approach with a case study method at SMPN 4 Limbangan Garut and SMP Adzzimat Da’i Indonesia Rancaekek Bandung, data were gathered through interviews, observations, and documentation, then analyzed with the Miles & Huberman interactive model. The results show that principals implement transformational leadership by: (1) exemplifying tolerant and inclusive behavior; (2) providing inspirational motivation through coaching and outreach on moderation values; (3) encouraging intellectual stimulation by promoting critical and reflective thinking on religious issues among teachers and students; (4) offering individualized guidance according to the needs of teachers and students; and (5) implementing moderation-based PAI learning through discussions, case studies, and integration of national values. Challenges such as teacher resistance, limited facilities, and diverse student backgrounds were addressed through training, effective communication, and collaboration. In conclusion, transformational leadership by school principals effectively internalizes religious moderation values in schools through PAI learning, thus contributing to the establishment of an inclusive, tolerant, and diversity-respecting school culture.